Does a history of depression actually mediate smoking‐related pain? Findings from a cross‐sectional general population‐based study. (27th February 2014) - van Hecke, O.; Torrance, N.; Cochrane, L.; Cavanagh, J.; Donnan, P.T.; Padmanabhan, S.; Porteous, D.J.; Hocking, L.; Smith, B.H.
Abstract Background Smokers report more pain and worse functioning. The evidence from pain clinics suggests that depression affects this relationship: The association between smoking and chronic pain is weakened when controlling for depression. This study explored the relationship between smoking, pain and depression in a large general population‐based cohort (Generation Scotland: Scottish Family Health Study). Methods Chronic pain measures (intensity, disability), self‐reported smoking status and a history of major depressive disorder (MDD) were analysed. A multivariate analysis of covariance determined whether smoking status was associated with both pain measures and a history of depressive illness. Using a statistical mediation model any mediating effect of depression on the relationship between smoking and chronic pain was sought. Results Of all 24, 024 participants, 30% (n = 7162) reported any chronic pain. Within this chronic pain group, 16% (n = 1158) had a history of MDD; 7108 had valid smoking data: 20% (n = 1408) were current smokers, 33% (n = 2351) former and 47% (n = 3349) never smokers. Current smokers demonstrated higher pain intensity and pain‐related disability scores compared with former and non‐smokers (p < 0.001 for all analyses). From the mediation model, the effect on pain intensity decreased (p < 0.001), indicating that the relationship between smoking and a history of depression contributes significantly to the effect of smoking on pain intensity. When applied to smoking‐related pain disability, there was no mediation effect. Conclusions In contrast to smokers treated in pain clinics, a history of MDD mediated the relationship between smoking and pain intensity, but not pain‐related disability in smokers in the community.